Studi Etnobotani Tentang Tanaman Obat di Desa Penfui Timur, Kabupaten Kupang: Ethnobotanic Study of Medicinal Plants in East Penfui Village, Kupang Regency - Putri, Lora Septrianda; So, Kristianto Wibison (Forestry Faculty of Hasanuddin University, 2026)
Indonesia is recognized as one of the world’s five megadiverse countries, possessing exceptionally high levels of biological diversity. This rich biodiversity makes Indonesia an important source for the development of traditional medicine. Identification of medicinal plants in Southeast Asia indicates that approximately 80% of medicinal plant species are found in Indonesia. Overall, Indonesia possesses 5,490 medicinal plant taxa, which account for about 20% of the world’s total medicinal plant species. This vast biological wealth reinforces Indonesia’s status as a megadiverse nation and highlights the importance of documenting traditional medicinal knowledge among local communities. As a megadiverse country, Indonesia makes significant contributions to traditional healing practices across various regions, including the East Nusa Tenggara (NTT) Province. This study aims to document the traditional knowledge of the people of Penfui Timur Village, Kupang Regency, regarding the use of local medicinal plants. The research specifically focuses on therapeutic (medicinal) uses of plants, excluding their spiritual or cultural applications. An ethnobotanical survey was conducted through observation, interviews, and visual documentation from May to June 2025. The results identified 26 medicinal plant species from 22 families used by the community to treat various ailments such as diarrhea, fever, wounds, bone fractures, white tongue, postpartum recovery, and gout. Leaves were the most commonly used plant part due to their easy accessibility and abundance of bioactive compounds. This local knowledge reflects the traditional wisdom of sustainable biological resource utilization and underscores its importance as a foundation for biodiversity conservation and the development of traditional medicine.